Fibrosing alveolitis and treatment with sulphasalazine. Issue 3 (March 1974) - Davies, Dewi; MacFarlane, Andrew
Abstract : A woman with ulcerative colitis was treated with sulphasalazine and prednisolone. After four months' treatment she began to get short of breath and she died a month later with severe subacute fibrosing alveolitis. It is believed that the lung disease was caused by sulphasalazine and that prednisolone was not able to prevent its development. A reversible form of lung disease has previously been attributed to this drug.